Plagiostenopterina sagarensis sp. nov. (Diptera: Platystomatidae: Platystomatinae) from Sunderban Biosphere Reserve, India with a key to Indian species - Roy, Sankarsan; Parui, Panchanan; Mitra, Bulganin (Zootaxa, 2017)
Plagiostenopterina sagarensis sp. nov., a new platystomatid species, from Sunderban biosphere reserve, India, is described with illustrations. A key to Indian species of genus Plagiostenopterina Hendel is also provided. The holotype and paratype specimens of the new species are deposited in the National Zoological Collections of Zoological Survey of India, Kolkata.